Histological changes in the endometrial of pregnant Sprague-Dawley rats under supplementation levels of n-6:n-3 fatty acid ratio - Abdulbari Kassem, Amira; Abu Bakar @ Zakaria, Md Zuki; Goh, Yong Meng; Mohamed Mustapha, Noordin (Academic Journals, 2011)
This study describes a changed uterine morphometry and its application to the endometrial structure of a pregnant rat. The number and the size of uterine gland and blood vessels changed during the pregnancy period of the rat. This effect on day 15 was significantly changed in the different groups. When the endometrial morphology was related to the circulating progesterone concentrations on day 15, it was observed that relationships were found on day 15 and a high progesterone concentration in the Diet 1:1 group was associated with an increased number of the uterine gland and blood vessel. Furthermore, animals in the Diet 1:30 group were slaughtered on day 15 and a low progesterone concentration on that same day was associated with the decreased uterine gland size, though a simultaneous decrease was found in the number of endometrial gland. In contrast, the number of implanted embryos was significantly lower in the Diet 3 group at 15 days of gestation The results suggest that the endometrial glands do not only grow and regress during the supplementation of high ratio n-6:n-3 fatty acids, but the number and size of the endometrial glands in the endometrial area are controlled by progesterone, which leads to changes in the structure and maintenance of the uterine during the pregnancy period.